ANALISIS PERENCANAAN PAJAK (TAX PLANNING) DALAM UPAYA MENINGKATKAN EFISIENSI BEBAN PAJAK PENGHASILAN BADAN PADA PT AKASHA WIRA INTERNASIONAL TBK - Herlisnawati, Dessy; Ahmad, Yola Fahmi (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2013)
ABSTRACTCompetition increases, the company is expected to make savings in all areas. One ofthe savings that can be done by the company is in the field of taxation, namely to streamlinethe burden of corporate income tax with tax planning. The purpose of this study was toinvestigate the implementation and effect of how the Tax Planning (Tax Planning) in Effortsto Increase the Efficiency of Corporate Income Tax Expense PT Akasha Wira InternationalTbk.The result showed that Tax Planning conducted by PT Akasha Wira International Tbkhas not been implemented properly, this can be seen from the persistence of the cost of taxexpendituresthat can still be maximized. Tax planning can still be maximized is consideringproviding tax benefits are included in the payroll, this planning can save the tax burden of4.5%. So that the tax burden can be saved then the company should consider providing taxbenefits to employees who entered into the payroll, thus increasing the operational costs ofsalaries, by itself will reduce tax payable.Keyword : Tax Planning, Equity, Income Tax, Efficiency.